Trust Memediasi Service Quality dan Financial Literacy terhadap Customer Loyality (Studi Kasus pada Nasabah Bank Syariah Indonesia di Kabupaten Kudus) - Afiq Faliqun Nawa; Muhammad Afiq Izzan Syafani; Indah Dewi Maharany (Journal of Islamic Economic Scholar, 2026)
This study aims to examine the effect of service quality and Islamic financial literacy on customer loyalty with trust as a mediating variable in Bank Syariah Indonesia digital banking services in Kudus Regency. The research employs a quantitative causal-associative approach using primary data collected through an online questionnaire from 115 BSI Mobile users selected by purposive sampling. The data were analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 4. The measurement model evaluation shows that most indicators meet the validity and reliability criteria, although Islamic financial literacy has a marginal AVE value and several discriminant validity values require attention. The structural model indicates that service quality has a positive and significant effect on customer loyalty and trust. Trust also has a positive and significant effect on customer loyalty. However, Islamic financial literacy does not have a significant direct effect on customer loyalty or trust. Trust significantly mediates the relationship between service quality and customer loyalty, but it does not mediate the relationship between Islamic financial literacy and customer loyalty. The findings highlight the importance of improving digital service quality and strengthening customer trust to enhance loyalty in Islamic banking.